Sealants in dentistry: outcomes of the ORCA saturday afternoon symposium 2007 (2010)
Sealants are a successful tool in caries prevention, but their role in preventive strategies after the caries decline has to be discussed. A survey of paediatric departments across Europe revealed that indications for pit and fissure sealants vary considerably, both nationally and internationally. Evidence for effectiveness of sealants in controlling caries in posterior teeth implies that sealants should be an integrated part of management of pit and fissure caries. Still, the indication for occlusal sealants seems to be shifting from primary prevention to a therapeutic decision for caries management of lesions in enamel and the outer part of the dentine. Sealants are also an interesting concept for caries management in approximal surfaces. Clinical trials suggest that novel techniques of sealing or infiltrating approximal lesions show promise. However, approximal sealing techniques are as complex to apply and time-consuming as approximal fillings. The article proposes guidelines for teaching on the use of sealants.